Hopeful - Gray, Shelley Shepard (Return to Sugarcreek, 2014)
"Miriam Zehr has worked at the Sugarcreek Inn longer than she cares to admit. The restaurant is a favorite of town residents as well as the many tourists who come to taste the famous Amish fare. Though she always tries to have a smile for every customer who comes in, deep down, Miriam knows something's missing... a family of her own. Miriam has never felt particularly beautiful, especially because she's always been a bit heavier than other girls her age. When the man she's pined after all her life suddenly seeks her out, she's thrilled to be noticed...until she realizes he's only asking for her help to get the attention of her neighbor, Mary Kathryn Hershberger. If Miriam helps Junior court Mary Kathryn, she'll get to spend a lot of time with him, but she may also lose him in the process. Are these few stolen moments worth the sacrifice? Is Miriam right to even hope for the life she dreams of?"